PEMBERDAYAAN BUMNAG SAIYO SAKATO MENUJU NAIK KELAS MELALUI DIGITALISASI KEUANGAN DAN INOVASI PENGEMASAN PRODUK - Silmi, Silmi; Fithri, Prima; Ramdany, Kevry; Furqan, Yasmin Ananta (Ensiklopedia of Journal, 2025)
Activities of this community service aims to enhance the capacity of BUMNAG managers in preparing digital-based financial reports. Financial digitalization has become a critical necessity in the modern era to improve transparency, accuracy, and efficiency in financial management. The methods employed in this program included interactive training, simulations of the SIAPIK application, and direct technical mentoring. The results of the activity demonstrated an improvement in participants' understanding and skills in operating the SIAPIK application for recording daily transactions and preparing monthly financial reports. Additionally, the application's effectiveness was evident in shorter recording times and easier real-time access to financial data. Participants also provided positive feedback regarding the application's features, which support their operational needs. In conclusion, this training and mentoring program successfully enhanced the financial digitalization capacity of BUMNAG Saiyo Sakato. Recommendations from this activity include the need for advanced training to deepen the utilization of SIAPIK's advanced features and integrate this application with other management systems. This is expected to support more professional and competitive BUMNAG governance.Keywords: Financial Digitalization, SIAPIK, BUMNAG, Digital Transformation, Financial Reporting